SOSIALISASI DAMPAK EKSPLOITASI SEKSUALITAS DAN EKONOMI ANAK MENJADI PENJUAL GORENGAN DI KOTA MAKASSAR INDONESIA - Ramlan, Herdianty; Kasnawi, Tahir; Manda, Darman; Kamaruddin, Syamsu; Syukur, Muhammad; Suardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Exploitation in any form always leads to harmful consequences or, at the very least, does not provide significant benefits. This includes exploitation of children. This service provides an explanation to parents and children about the various forms, internal and external factors, and mechanisms of child exploitation, particularly in the aspects of sexual and economic exploitation. Furthermore, it addresses exploitation carried out by parents against their own children. The results of this service show that parents and children have responded positively to the information regarding the forms, internal and external factors, and mechanisms of parental exploitation of children, as provided by the outreach team to the community. The information shared during this outreach covers various forms of child exploitation, including sexual exploitation of children, commercial exploitation of children, criminal exploitation of children, and economic exploitation of children. The socialization materials also address the internal and external factors that lead parents to exploit their children. Internal factors include parental fear, a child's willingness to help their parents, awareness, and the desire to meet personal needs, as well as the ease of finding work. External factors include social environments, parental motivations and coercion, lack of parental concern, and low socioeconomic status. The socialization materials cover the mechanisms of child exploitation, including physical and psychological violence, threats, rewards, and freedom of association. These are considered crucial for parents and children to understand to prevent parents from becoming perpetrators of child exploitation and children from becoming victims of their parents while trying to support their families, such as by selling fried snacks. Abstrak Eksploitasi dalam bentuk apapun selalu akan berujung pada hal – hal yang merugikan atau setidaknya tidak memberikan manfaat yang besar termasuk eksploitasi terhadap anak, pengabdian ini memberikan penjelasan kepada orang tua dan anak terkait dengan bentuk-bentuk, factor internal dan eksternal serta mekanisme eksploitasi anak dalam aspek eksploitasi seksual dan ekonomi, selain itu eksploitasi dilakukan oleh orang tua terhadap anaknya. Hasil pengabdian menunjukkan terkait dengan bentuk-bentuk, factor internal dan eksternal dan mekanisme eksploitasi orang tua terhadap anak mendapatkan respon positif dari orang tua dan anak yang mendapatkan sosialisasi dari tim pengabdian kepada masyarakat. Materi sosialisasi yang diberikan mencakup bentuk-bentuk eksploitasi terhadap anak yang terdiri dari eksploitasi seksualitas anak, ekspolitasi komersial anak, eksploitasi kriminalitas anak, eksploitasi ekonomi anak. Materi sosialisasi terkait factor internal dan eksternal orang tua melakukan eksploitasi terhadap anak mencakup ketakutan orang tua, kemauan anak membantu orang tua, kesadaran dan keinginan memenuhi kebutuhan pribadi dan pekerjaan yang mudah sebagai factor internal, sedangkan factor ekternalnya adalah lingkungan pergaulan, motivasi dan paksaan orang tua, kurangnya kepedulian orang tua dan rendahnya status sosial ekonomi orng tau. Materi sosialisasi mekanisme eksploitasi terhadap anak mencakup kekerasan fisik dan psikis, ancaman, pemberian hadiah dan kebebasan bergaul. Dianggap oleh orang tua dan anak merupakan hal yang sangat penting diketahui agar setiap orang tua tidak menjadi pelaku eksploitasi terhadap anak dan anak tidak menjadi korban dari orang tua dalam mecari nafkah menjadi penjual gorengan.